FEATURES OF PSYCHO-CORRECTIONAL WORK TO REDUCE FRUSTRATION AMONG STUDENTS OF HIGHER EDUCATIONAL INSTITUTIONS - Boymirzaeva D. D. (INTERNATIONAL JOURNAL OF RESEARCH IN COMMERCE, IT, ENGINEERING AND SOCIAL SCIENCES ISSN: 2349-7793 Impact Factor: 6.876, 2022)
This article describes a psycho-correctional program implemented in the course of psychological support for students, which is aimed at understanding and overcoming the destructive influence of frustration and its causes by students.